2019
DOI: 10.1002/pon.5034
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐related financial hardship among head and neck cancer survivors: Risk factors and associations with health‐related quality of life

Abstract: Objective Cancer survivors are susceptible to financial hardship. In head and neck cancer (HNC) survivors, we investigated (a) predictors for cancer‐related financial hardship and (b) associations between financial hardship and health‐related quality of life (HRQoL). Methods We conducted a cross‐sectional study in HNC survivors identified from the National Cancer Registry Ireland. HRQoL was based on the Functional Assessment for Cancer Therapy General (FACT‐G) plus Head and Neck Module (FACT‐HN). Objective can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 38 publications
4
64
3
Order By: Relevance
“…Altice et al conducted a systematic review of studies that described financial hardship experienced by cancer survivors and categorized existing measures into 3 categories: 1) material conditions (out‐of‐pocket costs, productivity loss, medical debt, or bankruptcy), 2) psychological responses (such as distress or worry from hardship), and 3) coping behaviors (skipped medications) . Among the studies they reviewed as well as other studies published after the review, most examined material conditions, and fewer examined coping behaviors or psychological responses. In our study, we used a measure of MFH that encompasses all 3 domains and has been used in previous studies among cancer survivors …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Altice et al conducted a systematic review of studies that described financial hardship experienced by cancer survivors and categorized existing measures into 3 categories: 1) material conditions (out‐of‐pocket costs, productivity loss, medical debt, or bankruptcy), 2) psychological responses (such as distress or worry from hardship), and 3) coping behaviors (skipped medications) . Among the studies they reviewed as well as other studies published after the review, most examined material conditions, and fewer examined coping behaviors or psychological responses. In our study, we used a measure of MFH that encompasses all 3 domains and has been used in previous studies among cancer survivors …”
Section: Discussionmentioning
confidence: 99%
“…Financial hardship can lead to unfavorable health care seeking behaviors, which could result in worse health outcomes and quality of life. Most studies only investigated this relation in the general cancer survivor population . Hastert et al reported differential forms of financial hardship experienced by African American versus white cancer survivors and found that it was associated with differences in limiting care because of cost .…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of financial hardship among cancer survivors is growing [19][20][21][22][23]. Survivors may be vulnerable to material financial hardship (henceforth financial stress) [24] due to outof-pocket costs as a result of the cancer diagnosis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…for medical care, supportive medications, travel to appointments) and lost income because of work absence during cancer treatment and rehabilitation [19]. Such financial stress appears particularly common in survivors with low income or financial stress before diagnosis [25][26][27][28] and has been associated with poor psychological well-being and worse quality of life (QoL) in a range of cancers [23,26,[29][30][31]. These findings have led to a recent call to increase knowledge of the relationship between financial stress and cancer-related symptoms or side effects, particularly those with physical manifestations [32]; better understanding of this could inform development and targeting of interventions among survivors.…”
Section: Introductionmentioning
confidence: 99%
“…A cancer diagnosis and its treatment influence the psychological well-being of the person diagnosed and may also have an effect on the relatives’ well-being 1–5. Moreover, evidence exists that a cancer diagnosis can also lead to occupational and financial hazards 6–8…”
Section: Introductionmentioning
confidence: 99%